The Impact of the New Hypertension Guidelines to Low-Dose Aspirin Prophylaxis Eligibility for the Prevention of Preeclampsia: A Cost-Benefit Analysis - Putra, Manesha; Balasooriya, Madagedara Maduka; Boscia, Alexander L.; Dalkiran, Evrim; Sokol, Robert J. (American Journal of Perinatology, 2019)
Objective American College of Cardiology and American Heart Association (ACC/AHA) published new guidelines which lower the cut-off for hypertension. We sought to evaluate the impact of these guidelines to cost and benefit of various low-dose aspirin prophylaxis approaches.Study Design Decision tree analysis was created using R software to evaluate four approaches to aspirin prophylaxis in the United States: no aspirin, United States Preventive Service Task Force (USPSTF) with Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC7) hypertension guidelines, USPSTF with ACC/AHA hypertension guidelines, as well as universal aspirin prophylaxis. This model was executed to simulate a hypothetical cohort of 4 million pregnant women in the United States.Results The new guidelines would expand the aspirin eligibility by 8% (76,953 women) in the USPSTF guidelines. Even with this increased eligibility, the USPSTF guidelines continue to be the approach with the most cost savings ($386.5 million) when compared with universal aspirin and no aspirin prophylaxis. The new hypertension guidelines are projected to increase the cost savings of the USPSTF approach by $9.4 million.Conclusion Despite the small change in aspirin prophylaxis, using ACC/AHA definition of hypertension still results in an annual cost-saving of $9.4 million in the United States when compared with JNC7.
Keywords: cost-benefit analysis; low-dose aspirin; preeclampsia prophylaxis; hypertension guidelines